Comparative analysis of the athletes` functional condition in cyclic and situational sports - Podrigalo, O. O.; Borisova, O. V.; Podrigalo, L. V.; Iermakov, S. S.; Romanenko, V. V.; Podavalenko, O. V.; Volodchenko, O. A.; Volodchenko, J. O. (Physical Education of Students, 2019)
Purpose: The athletic potential of athletes depends on functional condition parameters. They determine physical and mental performance. Their evaluation is part of the athletes` condition monitoring in many sports. The purpose of the study was the comparative analysis of the athletes` functional condition in cyclic and situational sports. Material: The study involved 31 students from specialized sport school aged 16-17. The participants were divided into two groups depending on the sport: 1st group - 20 martial arts athletes (Greco-Roman wrestling, freestyle wrestling, judo), 2nd group - 11 water sports athletes (swimming). The level of sportsmanship was Candidates and Masters of Sports. The following tests were applied: determination of the individual minute duration (IM) (s), measuring of a 10 cm segment, (cm), and determination of simple hand-eye coordination (SHEyC), (s), and simple hand-ear coordination (SHEaC), (s), "Figures memorizing" technique, solution of 10 sums. Results: The IM test results reflect the predominance of earlier completion of the test. This tendency more expressed in martial arts athletes. The results of measuring a segment were lower in all tests in the 1st group and in 9 tests in the 2nd group. The vision reaction in 4 tests out of 10 was better in martial arts athletes. The response to the auditory stimulus in 5 tests out of 10 and the average result was better in martial arts athletes. The results of figures memorizing test were most often average. The swimmers memorize significantly fewer figures according to 3 tests. The results of the solution of sums were similar. Conclusions: The use of a battery test allows giving a comparative analysis of the functional condition of different sports athletes. The stability of IM test results indicates sufficient adaptation reserves of the participants. The analysis of the results of the measuring of segment test allows evaluating the ability to spatial orientation as an important for success quality in martial arts and water sports. The importance of the response rate for the success of both martial arts athletes and swimmers confirmed. The martial arts athletes` results were significantly better. This confirms their ability to concentrate, to stay focused longer. The results allow considering the response rate to an auditory stimulus as an important indicator for predicting success. The figures memorizing test also reflects the specificity of sports. It illustrates the ability of athletes to control the environment, manage the situation. This ability is significantly better in martial arts athletes. The dynamics of solving sums results suggest some complexity with a long focusing on the swimmers and better parameters in martial arts athletes. The simplicity, accessibility and informative nature of the used tests suggest their use in the athletes` functional condition monitoring.